Scaffolding architecture: sustainable support for temporary disaster relief shelters in Malaysia / Farah Hanna Ahmad Fuad ... [et al.] - Ahmad Fuad, Farah Hanna; Hassan Naziri, Ahmad Faiz; Shahdan, Mohamad Shahin; Zainal Abidin, Mohammad Nazrin (2021)
Malaysia is prone to natural disasters such as floods that affect approximately 29,800 km2 every year when the monsoon season strikes (D/iya et al., 2014). This critical event leads to the urgent needs of temporary relief shelters that usually come in a form of available government building and public facilities to cater the dire needs of evacuees. Unfortunately, these shelters are not specifically designed for these crucial functions on account of economic and sustainability rationale as the relief centre will only be fully utilised in a short period of time per year. Privacy, dignity, and security are crucial factors in conducting a relief shelter because post- disaster may cause increasing mental and physical pressure on the flood victims (A. Bashawri et al., 2014). Mattresses and tents are some previous solutions that have been provided by the governments and NGOs. However, they are ineffective in catering various family sizes and ages, non- recyclable and require extra spaces to be stored when not in use. The incapability also will set off an uncomfortable environment for the evacuees especially when the relief shelters become crowded over the time (Nur Zawani Zahari & Ahmad Mustafa Hashim, 2018). This research aims to seek an alternative solution to cater privacy concerning issues in temporary disaster relief shelters whilst focusing on flexibility and sustainability as the key factors of the scheme. Scaffolding has recently been trending in providing functional short- term spaces including a gallery and temporary recreation centre (ArchDaily, 2020). Prominent characteristics of scaffolding will be studied alongside existing case- studies of scaffolding as an architectural material. Its potential needs to be unravelled as it is sustainable yet act as functional temporary ‘asylum’ for the flood victims in Malaysia.